Weakening of the stratospheric polar vortex by Arctic sea-ice loss - Kim, Baek-Min; Son, Seok-Woo; Min, Seung-Ki; Jeong, Jee-Hoon; Kim, Seong-Joong; Zhang, Xiangdong; Shim, Taehyoun; Yoon, Jin-Ho (Nature communications, 2014)
Successive cold winters of severely low temperatures in recent years have had critical social and economic impacts on the mid-latitude continents in the Northern Hemisphere. Although these cold winters are thought to be partly driven by dramatic losses of Arctic sea-ice, the mechanism that links sea-ice loss to cold winters remains a subject of debate. Here, by conducting observational analyses and model experiments, we show how Arctic sea-ice loss and cold winters in extra-polar regions are dynamically connected through the polar stratosphere. We find that decreased sea-ice cover during early winter months (November–December), especially over the Barents–Kara seas, enhances the upward propagation of planetary-scale waves with wavenumbers of 1 and 2, subsequently weakening the stratospheric polar vortex in mid-winter (January–February). The weakened polar vortex preferentially induces a negative phase of Arctic Oscillation at the surface, resulting in low temperatures in mid-latitudes. The mechanism behind the severely cold winters experienced by the mid-latitudes of the Northern Hemisphere in recent years is not fully understood. Here, the authors combine observational analyses and model experiments to reveal a dynamic connection between Arctic sea-ice cover and the polar stratosphere.